Change in Regime and Markov Models - Anders Rygh Swensen (Statistics Norway, Research Department, 1997)
In this paper we point out that using a two-state Markov chain to describe change in regime makes it difficult to interpret the model since there is a bias towards frequent shifts. However, by using a finite Markov chain with a transition matrix satisfying certain restrictions it is possible to circumvent the difficulty and at the same time use the established procedures for estimation and filtering. The methods are applied to a couple of time series from the Norwegian quarterly national accounts.
Keywords: C22; E32; 330; Change in regime; Markov-switching models; alternating renewal processes